Identification and Solutions for Cargo Loss on Self-Propelled Oil Barge (SPOB) Seroja V - Firmansyah, Achmad Amin; Sutoyo; Arleiny; Pribadi, Teguh (Journal of Engineering Science and Technology Management, 2026)
This study aims to identify the primary causes of cargo loss and to formulate effective solutions to address such losses aboard the Self Propelled Oil Barge (SPOB) Seroja V. The research employs a qualitative method with a descriptive approach to analyze operational discrepancies in the transport of Fatty Acid Methyl Ester (FAME). Data were collected through direct observation during onboard training (PRALA), semi-structured interviews with ship officers and cargo surveyors, and a comprehensive review of loading and discharging documentation. The findings reveal that cargo loss is driven by two distinct but interconnected factors: physical loss, characterized by evaporation, structural leakage, and residue accumulation; and apparent loss, resulting from measurement errors, calculation inaccuracies, and the use of uncalibrated measuring instruments. The study concludes that the unique physicochemical properties of FAME, combined with the aging infrastructure of the barge and the absence of automated monitoring systems, necessitate a robust intervention strategy involving technical remediation of tank integrity, stringent equipment calibration protocols, and the standardization of manual gauging procedures.